2018
DOI: 10.1038/s41598-018-28253-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Lysyl Oxidase-Like Protein 2 Expression in Pancreatic Cancer

Abstract: Lysyl oxidase (LOX) family genes, particularly lysyl oxidase-like protein 2 (LOXL2), have been implicated in carcinogenesis, metastasis, and the epithelial-to-mesenchymal transition (EMT) in various cancers. This study aimed to explore the clinical implications of LOXL2 expression in pancreatic cancer (PC) in the context of EMT status. LOX family mRNA expression was measured in PC cell lines, and LOXL2 protein levels were examined in surgical specimens resected from 170 patients with PC. Higher LOXL2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…22 Herein, we found that salidroside suppressed the expression of entire LOX family members, however, more effectively inhibited LOXL2 in a PC cell line (BxPC-3) (Figure 1). 22 Herein, we found that salidroside suppressed the expression of entire LOX family members, however, more effectively inhibited LOXL2 in a PC cell line (BxPC-3) (Figure 1).…”
Section: Discussionmentioning
confidence: 77%
“…22 Herein, we found that salidroside suppressed the expression of entire LOX family members, however, more effectively inhibited LOXL2 in a PC cell line (BxPC-3) (Figure 1). 22 Herein, we found that salidroside suppressed the expression of entire LOX family members, however, more effectively inhibited LOXL2 in a PC cell line (BxPC-3) (Figure 1).…”
Section: Discussionmentioning
confidence: 77%
“…We have previously reported that the EMT status is one of the independent prognostic factors for surgically resected PCs. The expression of lysyl oxidase homolog 2 (LOXL2), one of the important regulators of EMT, was significantly related to PC patients' survival and it is one of the putative therapeutic targets (4,20). In addition, evidence supports that EMT may mediate chemoresistance in PC and defining the EMT status of each PC patient might contribute to suitable multidisciplinary therapy (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…38 Among the LOX family members, LOXL2 has been considered to be a critical regulatory factor in tumor initiation and progression. 17,39,40 In addition, several LOXL2 splice variants have been found in esophageal squamous cell carcinoma, such as the variant lacking exon 13 and the variant with a deletion of 72 nucleotides, which contribute to tumor progression by a novel molecular mechanism distinct from canonical-type LOXL2. 17,39,40 In addition, several LOXL2 splice variants have been found in esophageal squamous cell carcinoma, such as the variant lacking exon 13 and the variant with a deletion of 72 nucleotides, which contribute to tumor progression by a novel molecular mechanism distinct from canonical-type LOXL2.…”
Section: Discussionmentioning
confidence: 99%
“…17 In previous studies, it has been demonstrated that LOXL2 was associated with poor prognosis in a variety of tumors and that overexpression of LOXL2 can promote the invasion and metastatic activity of cancer cells. 17,39,40 In addition, several LOXL2 splice variants have been found in esophageal squamous cell carcinoma, such as the variant lacking exon 13 and the variant with a deletion of 72 nucleotides, which contribute to tumor progression by a novel molecular mechanism distinct from canonical-type LOXL2. 19,22 In the current study, we used the loss-of-function and gain-of-function experiments to elucidate the role of the novel LOXL2 variant identified from TCGA HPVnegative HNSCC data.…”
Section: Discussionmentioning
confidence: 99%